2022
DOI: 10.1002/ped4.12339
|View full text |Cite
|
Sign up to set email alerts
|

An international study on implementation and facilitators and barriers for parent‐infant closeness in neonatal units

Abstract: van Goudoever, Johannes B and CROWN Study Group, (2022) An international study on implementation and facilitators and barriers for parent-infant closeness in neonatal units. Pediatric Investigation. pp. 1-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 64 publications
3
23
0
Order By: Relevance
“…An observational study 20 focusing on a survey to Swedish NICUs showed that, similarly to what we have described, most units did not provide meals nor opportunities for other family members to visit, and only around half units provided a bed/room to stay for parents. Another international study in European NICUs 21 described similar findings, with single family rooms, kitchen, bathroom or comfortable chairs mentioned as key facilitators for parent‐infant closeness. This study found that most units did not have single family rooms, and parents unfrequently participated on rounds.…”
Section: Discussionmentioning
confidence: 52%
“…An observational study 20 focusing on a survey to Swedish NICUs showed that, similarly to what we have described, most units did not provide meals nor opportunities for other family members to visit, and only around half units provided a bed/room to stay for parents. Another international study in European NICUs 21 described similar findings, with single family rooms, kitchen, bathroom or comfortable chairs mentioned as key facilitators for parent‐infant closeness. This study found that most units did not have single family rooms, and parents unfrequently participated on rounds.…”
Section: Discussionmentioning
confidence: 52%
“…Parent empowerment was often cited as a positive outcome of the mFICare program overall and of the individual components. Similar benefits have been seen with implementation of FICare in other countries, where it is also recognized that ongoing NICU investment in team education and coaching is needed to sustain a culture of parent–professional collaboration 23…”
Section: Discussionmentioning
confidence: 71%
“…Similar benefits have been seen with implementation of FICare in other countries, where it is also recognized that ongoing NICU investment in team education and coaching is needed to sustain a culture of parent-professional collaboration. 23…”
Section: Discussionmentioning
confidence: 99%
“…In countries across the world, family-integrated care (FICare) has become a standard of care, in which parents are integrated into the care team as equal members and as partners who deliver the majority of infant care in the NICU. 4-7 FICare results in benefits for both parents and infants, including demonstrated improvements in infant weight gain and exclusive breastfeeding rates, NICU length of stay, parent confidence and involvement in infant care, parent–infant bonding, and lower symptoms of parent stress, anxiety, and depression 1,4,8-13. Formal FICare programs do provide structured training to parents through the Parent Education pillar of FICare, in which parents learn how to care for their infant through required parent presence at the bedside (eg, 6-8 hours a day for 5 days a week), frequent small group education sessions, and participation in bedside rounds.…”
mentioning
confidence: 99%
“…[4][5][6][7] FICare results in benefits for both parents and infants, including demonstrated improvements in infant weight gain and exclusive breastfeeding rates, NICU length of stay, parent confidence and involvement in infant care, parent-infant bonding, and lower symptoms of parent stress, anxiety, and depression. 1,4,[8][9][10][11][12][13] Formal FICare programs do provide structured training to parents through the Parent Education pillar of FICare, in which parents learn how to care for their infant through required parent presence at the bedside (eg, 6-8 hours a day for 5 days a week), frequent small group education sessions, and participation in bedside rounds. Through prolonged parent presence and engagement with the care team, parents not only learn how to complete a wide range of infant care tasks but also learn how to comanage complex care in the NICU as members of the care team.…”
mentioning
confidence: 99%